2017
DOI: 10.1038/mp.2016.264
|View full text |Cite
|
Sign up to set email alerts
|

Selective increase of cerebrospinal fluid IL-6 during experimental systemic inflammation in humans: association with depressive symptoms

Abstract: Systemic inflammation is accompanied by profound behavioral and mood changes that resemble symptoms of depression. Findings in animals suggest that pro-inflammatory cytokines released by activated immune cells in the periphery evoke these behavioral symptoms by driving inflammatory changes in the brain. However, experimental data in humans are lacking. Here we demonstrate in healthy male volunteers (10 endotoxin treated, 8 placebo treated) that intravenous administration of low-dose endotoxin (0.8 ng/kg body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 61 publications
10
71
1
4
Order By: Relevance
“…Furthermore, another study reported increases in the proinflammatory cytokine IL-6 in human cerebrospinal fluid following endotoxin administration. 11 Together, these findings suggest that endotoxin administration and subsequent immune activation may end up impacting social behavior via central nervous system mechanisms.…”
Section: Sickness Behaviormentioning
confidence: 96%
“…Furthermore, another study reported increases in the proinflammatory cytokine IL-6 in human cerebrospinal fluid following endotoxin administration. 11 Together, these findings suggest that endotoxin administration and subsequent immune activation may end up impacting social behavior via central nervous system mechanisms.…”
Section: Sickness Behaviormentioning
confidence: 96%
“…Study by Engler et al directly tested the intravenous administration of low-dose endotoxin, one of the most important bacterial components contributing to the inflammatory process, in healthy male volunteers [40]. They found selective increase of IL-6 in the cerebrospinal fluid (CSF) and a strong association between the increase of CSF IL-6 levels and the endotoxin-induced mood deterioration, suggesting that increase in the central IL-6 concentrations may contribute to depression pathogenesis.…”
Section: Stress Depression and Il-6mentioning
confidence: 99%
“…Dies deckt sich mit Daten, die zeigen, dass Frauen im Vergleich zu Männern häufiger an affektiven Erkrankungen leiden [199,200]. Bedeutsam sind auch die Ergebnisse von Engler und Kollegen, die zeigen, dass die intravenöse Verabreichung von niedrig dosiertem Endotoxin (0,8 ng/kg Körpergewicht) in gesunden männlichen Probanden nicht nur einen signifikanten Anstieg der Plasmakonzentration von TNF, IL-6 und IL-10 bewirkt, sondern auch zu einem verzögerten aber verlässlichen und selektiven Anstieg von IL-6 in der Zerebrospinalflüssigkeit führt [201]. Letzterer war stark positiv mit der Schwere der Gemütsbeeinträchtigungen assoziiert [201], was darauf hindeutet, dass das Auftreten depressiver Symptome bei entzündlichen Erkrankungen in erster Linie auf einem Anstieg an IL-6 im Gehirn zurückzuführen sein könnte.…”
Section: Humandaten Deuten Eine Kausale Rolle Der Immunaktivierung Beunclassified